X-raying the Galactic interstellar medium: first all-sky correlation of X-ray and HI-data - Pradas, J. (2004)
The 3-D structure and composition of the Galactic interstellar medium can be deduced from soft X-ray absorption observations. For this purpose, we cross-correlate the ROSAT all-sky survey with the HI 21-cm line all-sky distribution provided by the Leiden/Dwingweloo and Instituto Argentino de Radioastronomía surveys. We analyse the data for the whole ROSAT-PSPC energy window (0.1 keV to 2.1 keV) to derive a consistent model of the diffuse X-ray background radiation. This approach allows to deduce the 3-D structure of X-ray absorbing and emitting gas and to constrain the distance to some high- (HVC) and intermediate-velocity cloud (IVC) complexes.